Strategi Satuan Siber Tentara Nasional Indonesia dalam Penguatan Infrastruktur Informasi Siber - Habibi, Habibi; Widodo, Pujo; Sianturi, Dohar (Journal of Current Research in Management, Policy, and Social Studies, 2025)
This study explores the strategic efforts of the Indonesian National Armed Forces (TNI) Cyber Unit in strengthening cyber information infrastructure to enhance the effectiveness of military information systems amid rising digital threats. The main problem lies in the suboptimal readiness of infrastructure and human resources, requiring comprehensive strategies to close the gap between actual and ideal conditions. The research applies a qualitative descriptive approach with a case study design, using in-depth interviews, observations, and document analysis. Data were thematically analyzed based on the Ends–Ways–Means framework, cybersecurity theory, threat theory, and asymmetric warfare theory. Findings indicate that the strategies implemented include layered defense, Zero Trust architecture, infrastructure modernization, certified human resource development, cross-branch integration, and collaboration with national and international institutions. These strategies reinforce the principles of confidentiality, integrity, and availability while addressing asymmetric cyber threats. Nevertheless, limitations remain in system interoperability, reliance on foreign technology, and uneven personnel readiness. Therefore, accelerated integration, technological self-reliance, and continuous capacity-building programs are recommended. In conclusion, the TNI Cyber Unit’s strategies provide a strong foundation for national cyber defense but require transformation toward a more proactive and integrated approach to effectively confront the evolving global threat landscape.